Central Office Supports for Data-Driven Talent Management Decisions: Evidence From the Implementation of New Systems for Measuring Teacher Effectiveness. (January 2017) - Grissom, Jason A.; Rubin, Mollie; Neumerski, Christine M.; Cannata, Marisa; Drake, Timothy A.; Goldring, Ellen; Schuermann, Patrick
School districts increasingly push school leaders to utilize multiple measures of teacher effectiveness, such as observation ratings or value-added scores, in making talent management decisions, including teacher hiring, assignment, support, and retention, but we know little about the local conditions that promote or impede these processes. We investigate the barriers to principals' use of teacher effectiveness measures in eight urban districts and charter management organizations that are investing in new systems for collecting such measures and making them available to school leaders and the supports central offices are building to help principals overcome those barriers. Interviews with more than 175 central and school leaders identify barriers in three main areas related to accessing measures, analyzing them, and taking action based on their analysis. Supports fall into four categories: professional development, connecting principals to sources of expertise, creating new structures or tools, and building a data use culture. Survey analysis suggests that indeed principals in high support systems perceive lower barriers to data use and report greater incorporation of teacher effectiveness measures into their talent management decisions.